The ketogenic diet as a treatment for traumatic brain injury: a scoping review. (21st March 2018) - McDougall, Alexandre; Bayley, Mark; Munce, Sarah EP
ABSTRACT: Traumatic brain injury (TBI) is a leading cause of morbidity and mortality worldwide. The ketogenic diet (KD) has been identified as a potential therapy to enhance recovery after TBI. The purpose of this study is to complete a scoping review and synthesize the evidence regarding the KD and its therapeutic effects in TBI. The methodological framework of Arksey and O'Malley was employed. Databases searched include Medline, EMBASE, CCRCT, CINAHL and WebOfScience. Two reviewers independently screened titles, abstracts and full texts in a two-step screening protocol to determine inclusion. Abstracted data included study setting and therapeutic mechanism. The KD was demonstrated to reduce cerebral oedema, apoptosis, improve cerebral metabolism and behavioural outcomes in rodent TBIs. Additionally, the KD affected rodent TBIs in an age-dependent manner. Due to a lack of relevant outcome measures, the human trials did not establish much evidence with respect to the KD as a treatment for TBI; only its safety was established. The KD is an effective treatment for TBI recovery in rats and shows potential in humans. Future research should aim to better elucidate the KD's mechanisms of action in human TBIs and determine if the KD's effectiveness on clinical outcomes can be reproduced in humans.